Laminated Wallboard Panels Made with Cellulose Nanofibrils as a Binder: Production and Properties - Hafez, Islam (Materials (Basel), 2020)
This study explored the development and characterization of laminated wallboard panels using renewable materials for building applications. The panels are based on cellulose nanofibrils (CNFs) as a binder and wood particles. Other additives included FiberLean(TM) (microfibrillated cellulose/calcium carbonate composite), starch and fire retardant (boric acid/borax). These panels are also intended to address the environmental concerns of commercial gypsum boards. The manufacturing of the panels is via a wet-based process; hence no initial drying was required to remove the water from the CNF. It was found that the dosage of CNF (and/or FiberLean(TM)) binder and the addition of starch had the largest impact upon the quality of the final product. The addition of starch was found more favorable in the presence of FiberLean(TM). The fire retardancy was induced by adding boric acid/borax (1:1). The burning test revealed that the panels treated with the fire retardant exhibited excellent burning properties comparable to that of gypsum board (inherently fire resistant). Interestingly, the addition of the boric acid/borax also appeared to increase the retention of starch in the system, leading to favorable mechanical properties.